Geochemical Analysis of a Glacial Lake Benson Varve Sequence, West-Central Minnesota - Mohr, A. R.; Johnson, G. C.; Cotter, J. F. P. (My University, 2010)
Glacial Lake Benson formed in western Minnesota as a meltwater from the retreating Des Moines Lobe filled low areas of the Minnesota River valley during the Late Wisconsin Glaciation. This study, analyzed the internal geochemistry of a 15-year Glacial Lake Benson varve sequence to investigate how geochemistry may change in a single location.
Color poster with text and diagrams.
Keywords: Glacial Lake Benson (Minn.); Geochemistry--Minnesota--Glacial Lake Benson; Glacial lakes--Minnesota; Varves--Minnesota; Posters